Multimodal strategies to hand hygiene in Ghanaian hospitals: a cross-sectional study in the Eastern Region of Ghana - Angela Ackon; Sofonias Asrat; Stephen Dajaan Dubik; Winfred Ofosu; Sally-Ann Ohene; Kingsly E Amegah; Ama Akyampomaa Owusu-Asare; Akosua Takyiwa Kwakye; Christiana Akufo; Joyce Amponsah; Hectoria Awekeya; Leslie Vander Puije; et al. (BMJ Publishing Group, 2024)
Background Hand hygiene (HH) is one of the core components of infection prevention and control and is critical for a high quality of care. Multimodal approaches are recommended to strengthen and drive HH systems in healthcare facilities (HCFs). We aimed to assess the extent of implementation of the WHO HH multimodal improvement strategy in HCFs in the Eastern Region of Ghana.Methods This study was a descriptive cross-sectional study involving 22 HCFs from 17 districts in the Eastern Region of Ghana. We collected data from 22 hospitals using the WHO Hand Hygiene Self-Assessment Framework (HHSAF). Data were analysed through descriptive statistics.Results The HHSAF median score denotes an intermediate HH implementation level (53.5%, IQR 48.8%-58.3%). Fourteen HCFs attained an intermediate level, five attained basic level, one attained advanced level and no facility exhibited inadequate HH implementation level. Evaluation and feedback had the highest score (64.3%, IQR 50%-71.4%), as ward-based audits for the availability of HH resources have become standard practice in many of the HCFs. Reminders in the workplace had the lowest score (33.3%, IQR 25.9%-37.0%), whereby less than half (46%) of the HCFs had posters explaining the indications for HH and the correct use of alcohol-based hand rubs. HH implementation level did not differ significantly among government (M=49.97, SD=12.30) and non-government (M=53.32, SD=18.73) facilities, (t (20)=−0.503, p=0.621).Conclusion Most HCFs had an intermediate HH implementation level. The provision of HH resources, including posters, HH rounds in patient care areas, introduction of HH corners, leadership, financial and organisational support are key elements for increased compliance with the WHO HH multimodal improvement strategy.